Know your place: Ethiopian children’s contributions to the household economy - Heissler, K; Porter, C (Young Lives, 2010)
This paper combines quantitative and qualitative analysis to develop a comprehensive and nuanced understanding of children’s work, in particular, the role of the household in determining work roles. Using a cohort study of children from Ethiopia, we examine the intra-household distribution of labour and make comparisons between households. Combining findings from these different perspectives reveals that work is fundamental to children’s lives and the functioning of their households, and is a source of pride, except when arduous or when not conforming to gender norms, which are quite pronounced – girls tend to work more in the household and boys in farming activities. Adults and children were asked to estimate the hours worked by children, and the answers were extremely similar, suggesting that adults do value the contribution of their children to the household. The nature and amount of work done by children is affected less by levels of household poverty than by shocks and adverse events, such as illness and death in the family – with girls being more affected by illness and the absence of mothers. Boys work more when households have more livestock. Overall, older girls work more than their siblings, and girls work more when there are younger brothers in the house. We argue that more attention should be paid by researchers and policymakers to the interdependence between children and adults within households; the way household and sibling composition, and birth order, shape work roles; and how these factors may interact with policy changes.